Various Intragastric Balloons Under Clinical Investigation - Seong Ji Choi; Hyuk Soon Choi (Korean Society of Gastrointestinal Endoscopy, 2018)
Obesity is a chronic disease with an exponentially increasing incidence rate, and its negative effects are well documented in numerous studies. As a result, the importance of bariatric therapy cannot be overemphasized, and many bariatric treatment methods with varying mechanisms have been developed. Of the available treatment methods, intragastric balloons, introduced in the 1980s, have been shown to be a safe and effective treatment modality; various intragastric balloon products have been developed and are currently being widely used in clinical settings. However, the disadvantages of intragastric balloons, such as unclear long-term weight loss benefits and complications experienced during insertion and removal, preclude their wider use. In this review, we discuss different intragastric balloon products, focusing on those under clinical investigation, and suggest future research directions.